Marketing strategies in micro-enterprises in the face of the Covid-19 contingency in Ciudad juárez, Mexico: a qualitative study (Revista de Investigaciones Universidad del Quindío, 2021)
The development of marketing strategies by companies appeared to be stable, however, it has been affected by contingency and confinement due to the Covid-19 pandemic. With official health instructions to prevent the spread of infection, confinement policies were established that restricted economic activities at the national level. Micro-entrepreneurs had to adapt or modify their marketing strategies in the face of restrictions, limiting direct interaction with consumers and users. The research aimed to determine the marketing strategies implemented by micro-enterprises for the sale of products and services in Ciudad Juarez, Mexico in the face of the contingency and confinement by Covid-19. The study was exploratory and descriptive, transversal, non-experimental, with qualitative approach based on the interpretative paradigm using the method of informed theory, using the interview technique. Some of the strategies implemented by micro-entrepreneurs were the use of the internet and social networks in advertising, physical barriers and distance pointing, the reduction of the capacity of people within establishments, work on demand or commissions, the continuous disinfection of the work areas, among others.
Keywords: Marketing strategies; micro-entrepreneurs; contingency; covid-19